Pengelolaan Zakat Di Aceh (Kajian Terhadap Qanun Aceh Nomor 10 Tahun 2018 Tentang Baitul Maal) - Makraja, Fahmi; Afifah, Nisa; Fitriyani, Elya; Al Fajri, Mirza (Maqasid: Jurnal Studi Hukum Islam, 2025)
Abstract: Based on law number 11 of 2006 concerning the Aceh government, Aceh has the privilege of regulating its government, including regional revenue distribution. Aceh issued Qanun number 10 of 2018 concerning baitul mal as a representation of regions that implement the provisions of Islamic law as the foundation of life. The aim of this research is to dissect and criticize as input for improvements related to several parts of this qanun which are considered irrelevant using a normative juridical approach and an Islamic approach based on literature study. The results of this research are that in article 102 regarding muzakki in the form of a business entity, the type of business is not explained in detail, then in article 104 (2) muzakki submits a power of attorney to the bank to deduct zakat from its savings, muzakki should be given freedom with faster payment transaction methods and It's easy, for example by using the payment method using Qris or using the mobile banking features available for zakat payments. On the other hand, the criteria for the type of business a person has must be explained, so that they can be categorized into muzakki or donation givers. Next is the riqab which is no longer relevant as an asnaf for zakat nowadays. The 'uqubat provisions in this qanun are very clear and detailed, starting from 'uqubat against muzakki to zakat managers who violate the rules. Keywords: Qanun Aceh, Zakat Management, Baitul Mal